A Simplified Method for Predicting Pattern Match Ratio - Tang, Xiaojuan; Duan, Huiqiong; Ding, Shuliang; Mao, Mengmeng (Frontiers in Psychology, 2021)
Cognitive diagnostic test design (CDTD) has a direct impact on the pattern match ratio (PMR) of examinees’ classification. It’s more helpful to know the quality of a test during the stage of the test design than after the exam is taken. The theoretical construct validity (TCV) is an index of the test quality which can be calculated without testing, and the relationship between the PMR and the TCV will be revealed. The TCV captures two aspects of the appeal of the test design:(a) simple paper-and-pen calculation-based items and (b) quick guidance for test assembly. The theoretical derivation and the Monte Carlo simulation show that the upper bound of the PMR is the TCV, which is equal to the slip free PMR. Furthermore, the TCV is related to the distribution of knowledge states and item categories, and has nothing to do with the number of items.